The answer is <span>2(–4y + 13) – 3y = –29
Step 1: Express </span><span>x from the second equation
Step 2: Substitute x into the first equation:
The system of equations is:
</span><span>2x – 3y = –29
x + 4y = 13
Step 1:
</span>The second equation is: x + 4y = 13
Rearrange it to get x: x = - 4y + 13
Step 2:
The first equation is: 2x – 3y = –29
The second equation is: x = - 4y + 13
Substitute x from the second equation into the first one:
2(-4y + 13) - 3y = -29
Therefore, the second choice is correct.
Answer:
(2,8)
Step-by-step explanation:
Answer:
41 21/25
Step-by-step explanation:
38 1/25 + 3 4/5 = 41 21/25
Answer:
Anything
Step-by-step explanation:
5n - 10 = 5n - 10
It doesn't matter what you put in for n, the equality can never be anything but an equality.
Suppose n = 10,000,000
Then 5*10,000,000 - 10 = 5*10,000,000